Development of a loop-mediated isothermal amplification assay for rapid detection of Burkholderia mallei - Mirzai, S; Safi, S; Mossavari, N; Afshar, D; Bolourchian, M (Cellular and Molecular Biology, 2016)
The present study was conducted to establish a Loop-mediated isothermal amplification (LAMP) technique for the rapid detection of B. mallei the etiologic agent of glanders, a highly contagious disease of equines. A set of six specific primers targeting integrase gene cluster were designed for the LAMP test. The reaction was optimized using different temperatures and time intervals. The specificity of the assay was evaluated using DNA from B.pseudomallei and Pseudomonas aeruginosa. The LAMP products were analyzed both visually and under UV light after electrophoresis. The optimized conditions were found to be at 63ºC for 60 min. The assay showed high specificity and sensitivity. It was concluded that the established LAMP assay is a rapid, sensitive and practical tool for detection of B. mallei and early diagnosis of glanders.